Pembelajaran Tari Pagar Pengantin untuk Siswa di Daerah Sumatera Selatan: Sebuah Kajian Literature Review - Citra Emalia; Suci Fajrina; Rosta Minawati; Iswandi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Pagar Pengantin Dance is a traditional cultural heritage from South Sumatra that contains profound aesthetic, moral, and social values. This dance originally functioned as part of the traditional wedding procession for the bride-to-be, symbolizing purity, gentleness, and readiness to enter married life. In the current educational context, the Pagar Pengantin Dance has begun to be integrated into arts and culture learning activities in schools. This learning not only plays a role in preserving regional dance arts, but also contributes to character formation, instilling moral values, and developing student creativity. This article discusses the urgency of implementing the Pagar Pengantin Dance learning in South Sumatran schools as a medium for cultural preservation, character building, and aesthetic education for the younger generation. This article is a literature review that discusses the implementation and urgency of learning the Pagar Pengantin Dance for students in the South Sumatra region. The Pagar Pengantin Dance as a traditional cultural heritage has high aesthetic, moral, and social values, which originally functioned as part of the traditional wedding procession symbolizing purity, gentleness, and readiness to live married life. Through a review of various literature, this study examines how the Pagar Pengantin Dance is integrated into arts and culture learning in schools as a means of preserving local culture, strengthening character, and developing student creativity. This study also highlights various pedagogical approaches and learning strategies used in transferring cultural values ​​through traditional dance. The review results indicate that learning the Pagar Pengantin Dance not only plays a role in maintaining the existence of regional culture but is also effective in shaping students' aesthetic sensitivity, morality, and cultural identity in the modern era.